Improved mesoscale segmentation of concrete from 3D X-ray images using contrast enhancers. (October 2018) - Carrara, P.; Kruse, R.; Bentz, D.P.; Lunardelli, M.; Leusmann, T.; Varady, P.A.; De Lorenzis, L.
Abstract: Obtaining the mesostructure of concrete from X-ray computed tomography (CT) requires segmentation of the data into distinct phases, a process complicated by the limited contrast between aggregates and mortar matrix. This paper explores the possibility to add baryte or hematite into the concrete mixture to enhance the contrast between cement paste and aggregates in CT, thus allowing for a semi-automatic segmentation. Raw and segmented CT images of plain and modified concrete mixtures are obtained and compared to assess the validity of the proposed approach. Characterization tests are also performed in order to ensure that the concrete characteristics are not appreciably affected by the presence of the enhancers.